Frequency-Dependent Cannabinoid Receptor-Independent Modulation of Glycine Receptors by Endocannabinoid 2-AG - Lozovaya, Natalia; Mukhtarov, Marat; Tsintsadze, Timur; Ledent, Catherine; Burnashev, Nail; Bregestovski, Piotr (Frontiers in Molecular Neuroscience, 2011)
Endocannabinoids are known as retrograde messengers, being released from the postsynaptic neuron and acting on specific presynaptic G-protein-coupled cannabinoid (CB) receptors to decrease neurotransmitter release. Also, at physiologically relevant concentrations cannabinoids can directly modulate the function of voltage-gated and receptor-operated ion channels. Using patch-clamp recording we analyzed the consequences of the direct action of an endocannabinoid, 2-arachidonoylglycerol (2-AG), on the functional properties of glycine receptor channels (GlyRs) and ionic currents in glycinergic synapses. At physiologically relevant concentrations (0.1-1 µM), 2-AG directly affected the functions of recombinant homomeric alpha1H GlyR: it inhibited peak amplitude and dramatically enhanced desensitization. The action of 2-AG on GlyR-mediated currents developed rapidly, within ~300 milliseconds. Addition of 1 µM 2-AG strongly facilitated the depression of glycine-induced currents during repetitive (4-10 Hz) application of short (2-ms duration) pulses of glycine to outside-out patches. In brainstem slices from CB1 receptor-knockout mice, 2-AG significantly decreased the extent of facilitation of synaptic currents in hypoglossal motoneurons during repetitive (10-20 Hz) stimulation. These observations suggest that endocannabinoids can modulate postsynaptic metaplasticity of glycinergic synaptic currents in a CB1 receptor-independent manner.